Analysis of cases of influenza A(H1N1) in Brazil and the state of Maranhão from 2009 to 2019 - Jaldin, Alejandro Elias Mouchrek (2021)
Since mid-2009, Brazil has been living with the influenza A (H1N1) pdm09 virus. In the pandemic period, the country reported 50,482 cases of Severe Acute Respiratory Syndrome (SARS) due to influenza A (H1N1) pdm09, among which 2,060 died. The objective of this study was to carry out an analysis of notified cases and deaths of the H1N1 flu in Brazil and in the State of Maranhão, from 2009 to 2019. This is an ecological study on influenza A (H1N1) pdm09. The data were obtained from the Notifiable Diseases Information System (SINAN), of the Ministry of Health (MS), available in the database of the Informatics Department of the Unified Health System - DATASUS. The seasonality of influenza A (H1N1) pdm09 was confirmed, except for the peculiarities of each region, mainly in the North and Midwest of the country. The prominent risk groups were adults> 60 years of age, heart disease, pulmonary disease and diabetes mellitus. Maranhão registered lower numbers than the national average, suggesting underreporting. The years 2016, 2018 and 2019 recorded the highest number of cases and deaths, excluding the year of the pandemic, in 2019 (10,625 / 1,987, 3,880 / 917 and 3,399 / 787, respectively). The states of the South and Southeast had the highest incidence in the entire period, with emphasis on Paraná and São Paulo. In view of the results, there was a need to reinforce the health surveillance system for influenza, through the creation of more sentinel units and strict data control; as well as optimization of vaccination campaigns, aiming to adapt to the reality found in each extreme of the country.